Adjunctive bevacizumab therapy in an equine corneal stromal invasive squamous cell carcinoma with a 53-months follow-up - Blohm, Klaas-Ole; Nell, Barbara (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2024)
A 17-year-old Appaloosa mare was referred for evaluation of presumed refractory keratitis of the left eye. Gross examination revealed ocular discomfort and corneal neovascularization with a nasal focal opacification affecting approximately 40% of the corneal surface. On ophthalmic examination, extensive subepithelial to mid-stromal vascular branching accompanied by a homogeneous white, dense opacification, which affected up to 80% of the total corneal thickness, were apparent. Signs of concurrent uveitis were absent. Deep-stromal lamellar keratectomy with a conjunctival pedicle graft was performed under general anesthesia. Histopathology confirmed a poorly differentiated corneal stromal invasive squamous cell carcinoma (SI-SCC) with neoplastic cell extension to the surgical margins. Postoperatively, 4 topical mitomycin C 0.04% chemotherapy cycles combined with oral firocoxib therapy were initiated. Seven months after surgery, regrowth of the SI-SCC was clinically suspected. A total volume of 1 ml bevacizumab 2.5% was administered in the standing sedated horse via 3 mid-stromal corneal injections. Four weeks later, intrastromal bevacizumab injections (ISBIs) were repeated, however, this time the solution was injected directly into the main corneal vessel branches.Seven weeks after the second ISBIs, the left eye was comfortable and significant remission of corneal vascularization and opacity was recognized. No recurrence has been noted for a follow-up period of more than 53 months.Equine SI-SCC usually has a very poor prognosis for globe maintenance. To the authors’ knowledge this is the first report of well-tolerated intrastromal antivascular endothelial growth factor adjunctive therapy with bevazicumab 2.5% and SI-SCC resolution after a multimodal treatment approach.
Keywords: Horse; ophthalmology; corneal neoplasia; microsurgery; anti-VEGF; multimodal therapy